Dari Keterampilan Menuju Kesuksesan: Membuka Potensi Kesiapan Kerja Generasi Z Melalui Kesejahteraan Psikologis - Sumampouw, Ruland Willy Jack; Talim, Fadli Ali; Fitriyani, Herlina Desia; Effendi, Syahrul; Wiliam, Andi (Lembaga Penelitian Universitas YARSI, 2026)
This study examines the influence of soft skills, hard skills, and internship experience on the work readiness of Generation Z, while exploring the role of psychological well-being. The research is motivated by the rising unemployment rate among university graduates, reflecting a mismatch between academic competencies and labor market demands. Using a quantitative approach, data were collected from Generation Z students and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study’s novelty lies in its integrated model that simultaneously investigates the effects of soft skills, hard skills, internship experience, and psychological well-being on work readiness. The results show that soft skills positively and significantly influence work readiness. Hard skills and internship experience significantly improve psychological well-being, whereas soft skills have no significant effect on psychological well-being. In addition, psychological well-being neither significantly affects work readiness nor mediates the relationships between soft skills, hard skills, internship experience, and work readiness. These findings suggest that Generation Z work readiness is primarily determined by competency-related factors rather than psychological mechanisms. Therefore, higher education institutions should prioritize soft-skill development and relevant internship programs to better equip students for labor market demands, while future research should explore other psychological and contextual factors influencing work readiness